Estudo das características epidemiológicas da deficiência visual dos pacientes matriculados no setor de baixa visão infantil do Hospital São Geraldo Hospital das Clínicas Universidade Federal de Minas Gerais - Cristina Helena Toledo de Paula (2013)
The epidemiological characteristics of 229 patients with visual impairment Low Vision Children's Service São Geraldo Hospital, Brazil, were studied retrospectively. Were reviewed the socio-demographic characteristics, associated disabilities, who first suspected the eye problem, the classification as a disease, group of diseases, anatomical region, etiology and causes avoidable and unavoidable; visual functions; refraction, optical correction prescription ; referral to the Institute for the Blind and treatment dropout. The mean age at first visit was 39.4 months, there was no difference in gender distribution and 64.6% of children held in the state. The family was the first to suspect the ophthalmic problem and 46.7% of patients had associated disabilities. The most prevalent diseases were congenital cataracts (14.0%), toxoplasmosis (13.5%) and congenital glaucoma (12.7%).Teamed up in groups of diseases and diagnoses showed the highest frequency of presentation were the malformations of the anterior segment (26.9%), retinal diseases (25.8%) and neurophthalmologIcal disease (23.6%) . The anatomical areas most affected were the eyeball normal (32.8%), retina (17.9%) and crystalline (14.8%) and the most prevalent etiologies were not determined (42.8%), the perinatal / neonatal factor (22.3%) and intrauterine factor (19.7%). The avoidable causes accounted for 63.7% of the sample. The esotropia was found in 33.6% of the sample, 30.6% in exotropia and nystagmus in 51.1% of children. Visual acuity was measured in both eyes, right eye and left eye, and the examination of visual acuity in both eyes for the age group 13-36 years and children with low visual center of origin was statistically significant . The most prevalent refractive error was hyperopia and astigmatism was present in approximately 30% of the sample. The use of visual correction was indicated in about 50% of children and compliance with glasses was high (77.3%). The referral institute for the blind occurred in 3.5% and abandonment of treatment in 15.7%. Was conclude that the determination of measures of children's eye health care at the primary and secondary level remains urgent in order to change quickly and permanently this picture. The tertiary care (habilitation / rehabilitation) should be included in an effective and automatic as soon as suspected and / or diagnosed visual impairment.